Approaches of New Entrepreneurship Development for Students Vocational Colleges - Thongyost, Narissara; Thawinkarn, Dawruwan; Somprach, Kanok-orn (Dhammathas Academic Journal, 2022)
The purpose of this research are: 1) to study the components of new entrepreneurship for vocational colleges, 2) to study the approaches and guidelines including Supporting factors and factors hindering entrepreneurship development for new vocational colleges By the Mixed Methods Approach, the research was divided into 2 phases. Phase 1 was to study of documents and related research (Documentary study) and in-depth interviews with 5experts to confirm the components. Phase 2 was the approaches 3 cases of bestpractice to get how to practice forthe entrepreneurship developmentof vocational colleges in 3 institutesGroup Discussion apporting factors and factor hindering entrepreneurship on new entrepreneurshipDesignated research areas in the number of 3 places, Research tools were questionnaires, interview form, document study form and observation form. Analyses the data by program computer and content analyses. The research result finds that: 1. The Components framework of new entrepreneurship for vocational colleges consistof six components: 1) Creativity 2) Innovation3) Critical Thinking 4) Digital Literacy 5) Persistent and 6) Risk Taking. 2. The results of the study of good practice guidelines. It was found that the following actions should be taken: 1) Developing the 7 key components of new entrepreneurship 2) Increasing the feature development activities in supplementary courses 3) Sending vocational learners for internships or internships in successful organizations or establishments 4) Organizing learning activities that instill in vocational learners the importance of being a new entrepreneur 5) Enhancement of competence in business management. As for the supporting factors and factors that hinder the entrepreneurship of new vocational colleges which has 6supporting factors and 5 obstacles.